Perancangan Sistem Informasi Surat Referendum Usulan Kenaikan Pangkat atau Jabatan Berbasis Web - Yudi Prabowo; Ike Pertiwi Windasari; Kodrat Iman Satoto (Jurnal Teknologi dan Sistem Komputer, 2015)
The rapid growth of information and communication technology (ICT) facilitate human activity. Senate of the Faculty of Engineering, University of Diponegoro , as the highest representative body of normative and within the faculty , has one of the tasks that provide feedback on a proposed referendum letter promotion . In the current procedure , the data is stored in the form of the proposed paper form . This method is less efficient , time-consuming addition , members often did not give his opinion because of forgotten or busy with other activities . The purpose of this study is to design a new, computerized information system that is capable of handling data storage process in the Senate , a notice of the proposed promotion, and management approval of the proposed increase in the post. Development of Information System was developed using FAST ( Framework for the Application of System Technique) . This information system development using PHP programming language ased on CodeIgniter framework . Storage and management of databases using a DBMS ( Database Management System MySQL . Testing Information System using User Acceptance testing , that using BlackBox Methodology . The results of this study is to produce a system that can accommodate the proposed promotion, responses senate , and spread in the form of an SMS message to the senate . So that this system can replace the system that is currently running are still less efficient and is manual .